INSTITUTIONAL BUYER ADOPTION OF B2B AGRICULTURAL E-COMMERCE: A SYSTEMATIC LITERATURE REVIEW USING THE UTAUT FRAMEWORK - Surya Danang; Supriyanto; Paske Victory Modaso; Fitayantri Tamau (JURNAL ILMIAH EDUNOMIKA, 2026)
Background: The digital transformation of agricultural supply chains in developing countries faces critical gaps in understanding how institutional buyers adopt B2B e-commerce platforms. Most existing studies focus on farmer (supply-side) adoption, leaving the demand-side perspective underexplored. Objective: This systematic literature review (SLR) aims to map the state of knowledge on B2B agricultural e-commerce adoption among institutional buyers through the UTAUT framework, and to identify research gaps that justify an empirical study in Eastern Indonesia. Methods: Following PRISMA 2020 protocol, we searched Scopus databases using six Boolean search strings. From 255 initial records, 3 duplicates were removed, yielding 252 unique articles. After screening (122 excluded) and eligibility assessment of 65 full-text articles (22 excluded), 43 final articles published from 2003 to 2026 were included. Results: Four thematic clusters emerged: (A) UTAUT in agrifood technology adoption, (B) B2B e-commerce and digital supply chains, (C) institutional buyers and digital platforms, and (D) digital agrifood context and gaps. Performance Expectancy (PE) and Social Influence (SI) are the most consistent predictors of adoption behavioral intention across 38 and 34 articles respectively. Trust emerges as a critical extension, especially in blockchain and platform adoption contexts. Conclusion: The literature reveals five critical gaps: (1) near-absence of demand-side B2B institutional buyer studies, (2) lack of UTAUT application in B2B agrifood buyer contexts, (3) minimal empirical evidence from Southeast Asia/Indonesia, (4) dominance of qualitative methods over quantitative SEM-PLS, and (5) weak linkage to national food security policy. This review provides the theoretical foundation and gap justification for an empirical study targeting institutional buyers (HORECA, modern markets, cooperatives).